2011
DOI: 10.4319/lom.2011.9.150
|View full text |Cite
|
Sign up to set email alerts
|

Physical fractionation of aquatic viral assemblages

Abstract: Aquatic viruses are extraordinarily diverse and have major influences on plankton ecology and evolution, but the majority of these viruses remain uncharacterized. Most viruses have not been cultivated and cultivationindependent means to explore viral diversity have provided only a fragmented view of viral genomic information. In this study, ultracentrifugation and chromatographic methods were evaluated for their ability to fractionate aquatic viruses based on their differing physical properties with the aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In the initial continuous cesium chloride (CsCl) gradient of the viral concentrate, a large portion of the viruses banded with little resolution over a broad range and at high densities (1.47–1.56 g ml −1 ; data not shown), an atypical result for this method [23]. The presence of a viscous whitish matter in this region of the gradient suggested that the viruses could be adsorbed to an unknown substance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the initial continuous cesium chloride (CsCl) gradient of the viral concentrate, a large portion of the viruses banded with little resolution over a broad range and at high densities (1.47–1.56 g ml −1 ; data not shown), an atypical result for this method [23]. The presence of a viscous whitish matter in this region of the gradient suggested that the viruses could be adsorbed to an unknown substance.…”
Section: Resultsmentioning
confidence: 99%
“…Continuous cesium chloride (CsCl) gradients were used as the first fractionation step to separate viruses from one another based on their differing buoyant densities [23]. The density of the viral concentrate was adjusted to 1.45 g ml −1 by the addition and dissolution of solid molecular grade CsCl (Fisher Scientific) and 10.5 ml of the resulting solution was deposited into a 12-ml polyallomer ultracentrifuge tube (Beckman Coulter).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several existing and emerging approaches will likely help identify and characterize non-tailed marine viruses. These include culture-based approaches (for example, targeted isolations with existing and new marine bacterial, archaeal and eukaryotic cultures), as well as new methods that either require only the host to be in culture (for example, viral tagging; Deng et al, 2012) or are completely cultivation-independent (for example, physical fractionation of viral assemblages; Bergeron et al, 2007;Steward and Rappé, 2007;Brum and Steward, 2011;Brum et al, 2013). The abundance and distribution of genetically characterized, non-tailed viruses could also be explored using phageFISH (Allers et al, 2013).…”
Section: Discussionmentioning
confidence: 99%